Durability of glucose-lowering effect of dulaglutide in patients with type 2 diabetes mellitus: A real-world data study - Kim, Hwi Seung; Cho, Yun Kyung; Kim, Myung Jin; Jung, Chang Hee; Park, Joong-Yeol; Lee, Woo Je (Frontiers in Endocrinology, 2022)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic, progressive disease requiring lifelong treatment, and durable medication is essential for maintaining stable glycemic control. This study aimed to evaluate the long-term efficacy of dulaglutide in participants who have continued the drug for more than one year. Methods: We conducted a retrospective study on 605 participants, who used dulaglutide for over one year between 2016 and 2020. Changes in glycosylated hemoglobin (HbA1c), fasting plasma glucose, and bodyweight from baseline to last prescription day were assessed. Adherence was evaluated by the proportion of days covered (PDC), and a PDC value ≥ 0.80 was considered adherent. Results: The mean age was 54.0 ± 11.1 years, and 46.1% were female. The mean baseline HbA1c, bodyweight, and duration of diabetes were 8.8% (72.7 mmol/mol), 75.6 kg, and 12.2 years, respectively. During the mean follow-up of 33.1 months, HbA1c and bodyweight decreased by 1.28% (14 mmol/mol, P < 0.001) and by 3.19 kg (P < 0.001), respectively. The participants were highly adherent with PDC ≥ 0.80 in 92.4% of the participants. Conclusion: In T2DM patients, long-term dulaglutide treatment was effective in maintaining HbA1c and weight reduction. Dulaglutide could be a favorable option of long-term treatment in real-world clinical practice.